The jubilee XX All-Ukrainian scientific Taliyev readings – a meeting of like-minded people - N. V. Maksymenko (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія)
On October 25, 2024, the Karazin Educational and Research Institute of Ecology will host the jubi-lee XX All-Ukrainian Scientific Taliev Readings, organized by the Department of Environmental Monitor-ing and Nature Conservation. The conference featured presentations on the following topics: the impact of war on environmental components, current problems of rational nature management and nature protection, and assessment of the ecological state of environmental components and complexes. In addition, the re-ports highlight scientific and educational issues of ecology and nature conservation in Ukraine.